Tourism Communication: Garuda Indonesia Airline In Improving Its Brand As A Tourism Transportation Service Provider - Engga Probi Endri (The Indonesian Journal of Communication Studies, 2025)
The development of the tourism sector intersects with other business sectors as it supports the tourism industry. Modern tourism management is a concept that defines tourism as a modern business product consisting of tourist destinations, the creative economy, transportation, hotels, recreation areas, and arts and cultural attractions, packaged in attractive tour packages for potential tourists. Modern tourism destinations are complex and capital-intensive, requiring business management and promotional activities. So, how does Garuda Indonesia enhance its brand as a tourism transportation service provider? This study aims to examine Tourism Communication: Garuda Indonesia's Brand Enhancement as a Tourism Transportation Service Provider using the concept of tourism transportation communication, which is part of tourism communication studies. The closest discipline to tourism communication is marketing communication. This study will use a case study with a qualitative approach. Data collection was conducted through interviews, documentation, and observation. Research informants were selected using purposive sampling techniques. The results of this study indicate that Garuda Indonesia is a tourism transportation service provider. The results show that the factors that determine passengers' choice of flying with Garuda are safety, price (in relation to facilities, service, and affordability), social (face-to-face, virtual, and relationships), comfort (physical and employees), membership (points, lounge, and redemption), and punctuality. Meanwhile, the motives for passengers choosing to fly with Garuda are achievement (punctuality and points), experience (comparison and aircraft), parental recognition, responsibility (family and work), and pleasure (service, physical, and travel).